Enhancing Electrocatalytic Activity of Perovskite Oxides by Tuning Cation Deficiency for Oxygen Reduction and Evolution Reactions - Zhu, Y.; Zhou, W.; Yu, J.; Chen, Y.; Liu, M.; Shao, Zongping (American Chemical Society, 2016)
Development of cost-effective and efficient electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is of prime importance to emerging renewable energy technologies. Here, we report a simple and effective strategy for enhancing ORR and OER electrocatalytic activity in alkaline solution by introducing A-site cation deficiency in LaFeO3 perovskite; the enhancement effect is more pronounced for the OER than the ORR. Among the A-site cation deficient perovskites studied, La0.95FeO3-δ (L0.95F) demonstrates the highest ORR and OER activity and, hence, the best bifunctionality. The dramatic enhancement is attributed to the creation of surface oxygen vacancies and a small amount of Fe4+ species. This work highlights the importance of tuning cation deficiency in perovskites as an effective strategy for enhancing ORR and OER activity for applications in various oxygen-based energy storage and conversion processes.